IMPROVING THE SUSTAINABILITY OF MSMES IN SEMARANG CITY WITH THE SUPPORT OF FINANCIAL TECHNOLOGY, FINANCIAL LITERACY AND FINANCIAL INCLUSION - Hidayatullah, Suryakusuma Kholid; Rachmansyah, Yanuar (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to analyze the influence of financial technology, financial literacy and financial inclusion in supporting the sustainability of MSMEs in the city of Semarang in the research period of 2024. In general, there are several factors that can affect the level of sustainability of the MSME sector business in the city of Semarang. In this study, an analysis was conducted on the support of the role of financial technology, financial literacy and financial inclusion in increasing the level of sustainability of the MSME sector business in the city of Semarang. Data needs were obtained from the results of questionnaire answers distributed to respondents of business actors or MSME actors in the city of Semarang. The results of this study are expected to provide information for every economic actor to know and understand the aspects of financial technology , financial literacy and financial inclusion in supporting the sustainability of the MSME sector business activities to create innovation and creativity of work programs in order to improve the performance of MSME businesses in the city of Semarang sustainably